2017
DOI: 10.21053/ceo.2015.01256
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Evaluation of Routine Nasopharynx Punch Biopsy in the Adult Population: Is It Really Necessary?

Abstract: Objectives To retrospectively evaluate the patients who underwent nasopharyngeal biopsy with imaging and biopsy results, who have or don’t have symptoms for nasopharyngeal pathology and to determine the ratio of the nasopharyngeal cancer cases and other pathologic conditions.Methods In this retrospective study, 983 patients who underwent endoscopic nasopharyngeal biopsy for symptomatic nasopharyngeal lesions were included. All pathological results, benign or malign was recorded and classified due to the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 14 publications
0
20
0
3
Order By: Relevance
“…The masses in this region are important for adults in terms of malignancy. The symptoms of nasopharyngeal malignancy are not specific, and, additionally, due to its localization, patients generally present in the late period, and this causes delay in treatment [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The masses in this region are important for adults in terms of malignancy. The symptoms of nasopharyngeal malignancy are not specific, and, additionally, due to its localization, patients generally present in the late period, and this causes delay in treatment [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this subject, in the study of King et al, 95% accuracy rate, 100% sensitive, 93% specificity, and 87% positive predictive value were determined for nasopharyngeal MRII in primary nasopharyngeal cancers. Bercin et al stated that the sensitivity of MRI was 88.2% in nasopharyngeal malignancies [ 4 , 8 ]. In our study, MRI was also found to be the most preferred imaging method.…”
Section: Discussionmentioning
confidence: 99%
“…The patients underwent careful physical and endoscopic examinations at every clinic visit, scheduled every 1–3 months during the first year, every 2–4 months during the second year, every 4–6 months during the third, fourth, and fifth years, and annually thereafter (Ahn et al., ; Denaro, Merlano & Russi, ). Any recurrent or new tumors were confirmed by biopsies and specific additional diagnostic tests including CT/MRI and/or 18 F‐FDG PET/CT scanning (Bercin et al., ). Second primary cancer was defined according to the criteria proposed by the National Cancer Institute as follows: if it was of different pathology or in a different location from the index cancer, or developed in the same region after more than 5 years of the index cancer diagnosis (Curtis et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Amacımız, 9 yıllık bir süreçte şüpheli nazofaringeal lezyonları tanımlamak için alınan biyopsi sonuçlarını klinik ve patolojik verilerle karşılaştırmak. (6,11). Literatürle uyumlu olarak çalışmamızda izlenen tornwaldt kisti benign lezyonların yaklaşık %1'ini (5/464) oluşturmaktaydı.…”
Section: Introductionunclassified
“…Erken dönemde tanı konduğu takdirde küratif olabilen bu tümörlerin yarısından fazlası ileri evrede tanı almaktadır (12). Yapılan önceki çalışmalarda nazofarinkste izlenen en sık malign tümörler sırasıyla nazofarinks ve hematolenfoid malignite olduğu bildirilmiştir (4,6,11,13,14). Literatürle uyumlu olarak malign olgularımızın %77.4'ü nazofaringeal karsinom ve %21.1'i ise hematolenfoid maligniteden oluşmaktaydı.…”
Section: Introductionunclassified